ENHANCING THE DEVELOPMENT OF WRITING SKILLS IN ESP CADETS: STRATEGIES AND APPROACHES - Rashidova , Munavvar Xaydarovna; Namozova , Dilnoza Berdimurotovna (Innovative Development in Educational Activities, 2024)
This review article explores strategies and approaches for enhancing the development of writing skills in English for Specific Purposes (ESP) cadets. It examines the importance of needs analysis, task-based approaches, and process-based instruction in fostering writing proficiency. Collaborative writing, peer feedback, the integration of technology, and vocabulary and grammar instruction are discussed as effective techniques. The article emphasizes the significance of genre analysis and genre-based approaches in understanding the specific requirements of ESP writing. By employing these strategies, instructors and institutions can empower cadets to become competent writers in their respective professional fields.